Implementasi Bahan Ajar Pendidikan Agama Islam Kelas VIII Berbasis Multi Modal di SMP Pesantren Raudlatul Ulum Ganjaran Gondanglegi Malang - Humayroh; Luqman Hakim (Mu'allim, 2026)
This research examines the development of Islamic Education (PAI) teaching materials based on a multimodal approach at SMP Pesantren Raudlatul Ulum Ganjaran. The study aims to analyze the process of developing multimodal teaching materials, their implementation in learning activities, and their effectiveness in improving students’ understanding and engagement. Employing a qualitative research method with a case study approach, data were collected through observations, interviews, and documentation involving teachers and students, as well as analysis of the developed teaching materials. The multimodal approach integrates textual, audio, and visual media to support PAI instruction. The findings indicate that multimodal teaching materials significantly enhance students’ cognitive comprehension, learning motivation, and emotional engagement, resulting in more interactive learning experiences. The success of implementation is strongly influenced by teachers’ active roles as material designers and evaluators, supported by institutional resources. Despite challenges such as limited budgets and less optimal evaluation methods, the use of technology-based assessments and student involvement in material development emerged as effective strategies. Overall, the multimodal approach demonstrates strong potential for broader application in other educational institutions, particularly pesantren, to improve the quality of PAI learning.